Climate change and water IPCC Technical paper VI - Intergovernmental Panel on Climate Change (IPCC Secretariat, 2008)
This technical paper was produced by the Intergovernmental Panel on Climate Change (IPCC) in response to work carried out to address the cross cutting theme of water in relation to climate change. The topics covered include freshwater; sea level rise and its impacts on freshwater in coastal areas; biophysical and socio-economic systems; and the relationship between climate change and freshwater resources.